Preventing sexual assault on college campuses: who cares? - Ulmer, Ashley (Kansas State University, 2019)
This study used a survey to gather information from 112 women on Kansas State University’s campus on the topic of sexual assault. This study attempted to fill in the gap of research concerning sexual assault, reporting, and student engagement with university prevention initiatives. The key findings of this study show that students are willing to learn about sexual assault, and that high levels of university involvement and high levels of perceived self-efficacy lead to an increase in a student’s willingness to report cases of sexual assault. Future research should explore a branding campaign for successful sexual assault prevention initiatives, while looking into the concept of self-defense as a viable addition to current campus offerings.
Keywords: Violence; Rape; Sexual assault reporting; Campus policy; Self-defense trainingCampus safety